2012
DOI: 10.5667/tang.2011.0002
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of traditional Korean medicine, Jeechool-Whan in allergic rhinitis model

Abstract: Jeechool-Whan (JW) is a prescription of Ponciri Fructus Immaturus and Atractylodis Rhizoma Alba and improves the functions of the stomach and the spleen. Although it is said in Korean Medicine that the spleen and the stomach are the roots of the body's resistance, the meaning of 'improving the spleen and the stomach' is very comprehensive. Moreover, there are lots of drugs that are said to improve the spleen and the stomach, and the number of prescriptions using these drugs is huge. In this study, we focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Choi et al [27] reported that hesperidin reduced the expression of TNF-α by suppressing HIF-1α in mast cells. TNF-α is released from mast cells by degranulation and aggravates allergic symptoms by inducing neutrophil chemotaxis and the production of other inflammatory cytokines [28,29,30]. Our results show that Buk music down-regulated TNF-α protein levels, which suggests Buk music down-regulated TNF-α by inhibiting HIF-1 activation.…”
Section: Discussionsupporting
confidence: 57%
“…Choi et al [27] reported that hesperidin reduced the expression of TNF-α by suppressing HIF-1α in mast cells. TNF-α is released from mast cells by degranulation and aggravates allergic symptoms by inducing neutrophil chemotaxis and the production of other inflammatory cytokines [28,29,30]. Our results show that Buk music down-regulated TNF-α protein levels, which suggests Buk music down-regulated TNF-α by inhibiting HIF-1 activation.…”
Section: Discussionsupporting
confidence: 57%
“…We used the methods of Moon et al (2012) and Oh et al (2012), using an easy-BLUE™ RNA extraction kit (iNtRON Biotech, Republic of Korea) and isolated the total RNA from HMC-1 cells in accordance with the manufacturer's specification. The concentrations of total RNA in the final elutes were determined by spectrophotometer.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Anamentioning
confidence: 99%
“…Hesperidin, an active component of KMP6 potently regulates stem cell factor (SCF)-induced migration through the hindering of SCF and c-kit binding in mast cells . Recently, we also reported that KMP6 has the regulatory effect in AR and AD animal model (Han et al, 2012;Oh et al, 2012a). However, it has not been sufficiently clarified how KMP6 and its active compound, hesperidin, modulate the responses of mast cells.…”
Section: Introductionmentioning
confidence: 99%